Legal Policy of Anti-Corruption Supervisor Design: A New Anti-Corruption Model in Indonesia - Sidik Sunaryo; Asrul Ibrahim Nur (BESTUUR, 2022)
Corruption is a fact of life in Indonesia and has a significant negative impact. The malicious intention of corruption in Indonesia has normatively shifted in terms of its meaning, adjusting to its opportunity. However, the increase in corruption in Indonesia is not accompanied by a legal policy of anti-corruption supervisor design. This study analyzes the legal procedure of strengthening supervision for corruption prevention in realizing good governance. The results indicate that the derived meaning of malicious intention of corruption in the old order, new order, and reform era gradually reduces the significance of adversarial nature from the perspective of public morality and the state's ideology. The Corruption Eradication Commission has been given authority to prevent and prosecute criminal acts of corruption. Establishing anti-corruption institutions in the regions serves as an anti-corruption enforcement agency and a control and monitoring system for government administration in all agencies to achieve good governance.